(WIP) "StopScopeCreep", Using Interprofessional Education to Tackle the Territorialism Conflict: Presenter(s): Judson Mead, Idaho State University, United States. (April 2023) - Papa, Jared
Abstract : Background: In 2020, the American Medical Association initiated an information campaign entitled "StopScopeCreep". The program was a response to broadening scopes of practice of health care professionals during the COVID-19 pandemic. Territorialism between health professions has been ongoing for decades yet rarely addressed in the education of health professionals. Together with the Idaho College of Osteopathic Medicine, the physician assistant program at Idaho State University designed an Interprofessional Education (IPE) activity to help students learn how to navigate the conflicts of territorialism among health professions. The IPE activity involved a mixed group of health care students: DO, PA, pharmacy, and speech pathology. This presentation will share and assess the concept of using IPE for teaching students about territorialism while creating a model to foster productive dialogues between students in medicine. Methods: Students were presented reading material and a lecture on the topic, followed by a small group discussion. Students scored their awareness of the topic prior to and after the IPE. They were also asked to describe how the presentation and IPE changed their perspective on the topic. Findings: Results from the 2021 IPE showed that 54% of students said their awareness of the topic improved, 40% did not improve, and 4% worsened. Overall the feedback was very positive. Many students felt the activity was engaging, educational and effective at establishing positive communication between student groups. Findings: from an IPE in 2022 will be included during the oral presentation. Discussion: Results showed that providing controversial and relevant subjects can engage students in discussion, educate them on complicated issues in healthcare and provide an avenue to educate fellow future colleagues on their roles in medicine. The IPE designed on scope of practice provides an effective model for other educators to conduct similar educational activities on controversial topics.